READDRESSING THE TRANSLATION OF NEAR SYNONYMY IN THE GLORIOUS QUR’AN - Adel El-Sayed Hassan (European Scientific Journal, ESJ, 2014)
Complete synonymy is known to be rare or almost non-existent, as it is not easy to find words with identical denotations and/or connotations. In contrast, incomplete or near synonymy is plentiful in almost all types of lexis, in general, and the lexis of the Glorious Qur’an, in particular. In addition to its abundance, near synonymy is a source of richness in the ST, a feature that challenges translators and makes it quite difficult for them to produce equally rich TT, with communicatively equivalent lexical items. This ST richness is probably among the main reasons why many translators fail to capture the shades of overlapping denotations or suggestive connotations of the lexical items used in the ST. This study attempts to explore the notion of synonymy in both Arabic and English. It also seeks to assess the accuracy of the translations of selected near synonyms offered by a number of translations of the meanings of the Glorious Qur’an. The adequacy of the translations of the near synonyms in question is judged according to their interpretations by Arab and non-Arab linguists and exegetes as well as to the context in which they occur. The study concludes that the translators under study have limitations in translating the near synonyms adequately. Therefore, it proposes more appropriate renditions of those synonyms, thus minimizing the chances of distortion which other defective translations are riddled with.